2009
DOI: 10.4269/ajtmh.2009.80.51
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Chitinase Genotypes in a Patient with an Amebic Liver Abscess: A Case Report

Abstract: The present work deals with the identification of a patient with two liver abscesses containing two different strains of Entamoeba histolytica, as defined by chitinase gene plymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Examination of the genotypes of E. histolytica in stool- and liver abscess-derived samples from the same patients was recently performed, and the intestinal and liver abscess amebae were genetically distinct [18]. A recent report also uncovered two simultaneous and independent abscesses in the same patient, where a different genotype was found in each abscess [19]. Together, these results support a role of the parasite genotype in virulence, and further suggest that there is a genetic bottleneck where only certain genotypes are capable of causing abscesses.…”
Section: Variable Outcome Of Diseasementioning
confidence: 99%
“…Examination of the genotypes of E. histolytica in stool- and liver abscess-derived samples from the same patients was recently performed, and the intestinal and liver abscess amebae were genetically distinct [18]. A recent report also uncovered two simultaneous and independent abscesses in the same patient, where a different genotype was found in each abscess [19]. Together, these results support a role of the parasite genotype in virulence, and further suggest that there is a genetic bottleneck where only certain genotypes are capable of causing abscesses.…”
Section: Variable Outcome Of Diseasementioning
confidence: 99%
“…[ 50 ] Other authors also detected different genotypes of E. histolytica trophozoites isolated from two distinct amebic liver abscesses from the same patient. [ 51 ] As with certain E. histolytica strains, E. dispar strains may also exhibit varied biological behavior as a result of genetic diversity. [ 43 ]…”
Section: Introductionmentioning
confidence: 99%
“…These studies analyzed the coding and non-coding DNA regions of these species, allowing a better understanding of the heterogeneous character of the parasite infection sources as well as the complexity of the human asymptomatic infection and the disease. Recent reports showing the differences in the genotypes of E. histolytica isolates from fecal samples and samples from amebic liver abscesses obtained from the same patient [13] and the detection of different genotypes of E. histolytica detected in a patient with two simultaneous and independent amebic abscesses of the liver [14] are two examples of this complexity. Several hypotheses were considered in these studies to explain the observed genotype variations, ranging from the ingestion of inoculums containing more than one E. histolytica and/or E. dispar genotypes (strains) to the possible existence of some kind of organ tropism or a possible recombination phenomenon during intestinal colonization.…”
Section: Introductionmentioning
confidence: 99%